Antimicrobial activities of coriander in chicken meat products: A review - Morshdy, Alaa Eldin M.A.; Morsy, Doha M.A.; Mahmoud, Abdallah F.A.; Darwish, Wageh (Journal of Advanced Veterinary Research, 2024)
Chicken meat products contribute significantly as a fairly priced substitute for red meat, which is critically undersupplied in Egypt. This type of meat is high in animal protein, vital amino acids, and trace elements. Furthermore, as a result of rapid improvements in food processing and technology, a variety of chicken meat products, including as chicken burgers, chicken fillets, chicken sandwiches, chicken nuggets, and chicken panne, were manufactured and released into the chicken meat markets. Such key products are defined by their distinct flavor and aroma, which captivates buyers, particularly children. Microorganisms can contaminate chicken meat products at any stage of production, including raw material preparation, manufacture, distribution, and storage. As a result, chicken products are regarded to be a possible source of bacteria that cause food poisoning, such as Staphylococcus aureus (S. aureus) and Salmonella spp. Essential oils derived from the coriander plant (Coriandrum sativum L.), either from the seeds or the leaves, are among the most extensively utilized. Coriander and coriander essential oils are antibacterial, anti-oxidant, anti-diabetic, anxiolytic, anti-epileptic, depressive, anti-mutagenic, anti-inflammatory, antidyslipidemic, antihypertensive, neuroprotective, and diuretic. In this review, we threw the light on the microbial contamination of chicken meat and meat products in Egypt and worldwide. Besides, the antibacterial activities of coriander will be reviewed.